2022
DOI: 10.13164/mendel.2022.2.025
|View full text |Cite
|
Sign up to set email alerts
|

USTW Vs. STW: A Comparative Analysis for Exam Question Classification based on Bloom’s Taxonomy

Abstract: Bloom’s Taxonomy (BT) is widely used in educational institutions to produce high-quality exam papers to evaluate students’ knowledge at different cognitive levels. However, manual question labeling takes a long time, and not all evaluators are familiar with BT. The researchers worked to automate the exam question classification process based on BT as a solution. Enhancement in term weighting is one of the ways to increase classification accuracy while working with text data. However, all the past work on the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Taxonomy is another word for classification. According to Gani et al (2023) & Pratiwi (2015, taxonomy implies a hierarchy of classifications based on basic principles or rules. Bloom's taxonomy is a classification system for cognitive thinking skills.…”
Section: Bloom's Taxonomymentioning
confidence: 99%
See 1 more Smart Citation
“…Taxonomy is another word for classification. According to Gani et al (2023) & Pratiwi (2015, taxonomy implies a hierarchy of classifications based on basic principles or rules. Bloom's taxonomy is a classification system for cognitive thinking skills.…”
Section: Bloom's Taxonomymentioning
confidence: 99%
“…Content analysis is a simple research approach that is used to analyze books, documents, etc. Content analysis is a type of qualitative study, which is defined as "a research method for the subjective interpretation of the content of text data through the systematic classification process of coding and identifying themes and patterns" (Gani et al, 2023;Hsieh & Shannon, 2005). Further, it is systematic reading for making replicable and valid inferences from texts or other symbolic matters.…”
Section: Research Toolsmentioning
confidence: 99%
“…Karamustafaoglu et al have classified biology questions as per Bloom's taxonomy by Biology teachers [47]. Various approaches, including naïve bayes, laplace smoothing [48], artificial neural networks [49], CNN [50], pre-trained language model [51], and rule-base [52] have been employed for question classification. The various types of context-based and grammarbased questions generated through the AQG model are depicted in Figures 5 and 6.…”
Section: 3mapping Of Questions With Blooms Taxonomymentioning
confidence: 99%
“…Since that time, RBT has been used officially to construct the curriculums considering the cognitive levels of learners. RBT has certain classifications which are remembering, understanding, applying, analysing, evaluating and creating (Gani, 2023). It can be clearly observed that it emphasizes the value of laying solid background before driving the learners to produce.…”
Section: Literature Reviewmentioning
confidence: 99%